2019
DOI: 10.3390/su11061513
|View full text |Cite
|
Sign up to set email alerts
|

Response of Nitrogen Losses to Excessive Nitrogen Fertilizer Application in Intensive Greenhouse Vegetable Production

Abstract: Excessive nitrogen fertilizer application in greenhouse vegetable production (GVP) is of scientific and public concern because of its significance to international environmental sustainability. We conducted a meta-analysis using 1174 paired observations from 69 publications on the effects of nitrogen fertilizer application and reducing nitrogen fertilizer application on the nitrogen losses on a broad scale. We found that the increase in nitrogen loss is much higher than that in production gain caused by excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 46 publications
(60 reference statements)
0
31
0
1
Order By: Relevance
“…Moreover, the N rate for split application in summer maize was 310 kg hm −2 in the vertisol soil of Anhui province, whereas the NUE in maize was only 23% [6]. Excessive N application resulted in a large amount of N losses in forms such as surface runoff, ammonia volatilization, nitrate leaching, and denitrification, thus causing serious ecological and environmental problems [1,28,31,32]. Therefore, on the basis of ensuring high yield, reducing N rate and minimizing N loss is one of the important research directions in agricultural sustainability.…”
Section: Optimal Nitrogen Rate Of Rzf For Summer Maizementioning
confidence: 99%
“…Moreover, the N rate for split application in summer maize was 310 kg hm −2 in the vertisol soil of Anhui province, whereas the NUE in maize was only 23% [6]. Excessive N application resulted in a large amount of N losses in forms such as surface runoff, ammonia volatilization, nitrate leaching, and denitrification, thus causing serious ecological and environmental problems [1,28,31,32]. Therefore, on the basis of ensuring high yield, reducing N rate and minimizing N loss is one of the important research directions in agricultural sustainability.…”
Section: Optimal Nitrogen Rate Of Rzf For Summer Maizementioning
confidence: 99%
“…In fertilizer applications not suitable for the technique, the nitrogen is leaching from the soil or away from the gaseous state and the nutrients such as phosphorus and potassium are transformed into non-volatile forms. As a matter of fact, while 50% of the nitrogen applied to the soil is lost in various ways, 90% of the phosphorus cannot be taken by plants [10,11]. Studies have shown that fertilizer nitrogen use efficiency is very low for wheat, paddy and corn, and nitrogen utilization rate is between 29 and 42% [12].…”
Section: Managing Soil Nutrientsmentioning
confidence: 99%
“…Es importante destacar que un exceso de N en el sistema de producción contribuye a la contaminación del ambiente, especialmente en los trópicos, donde la eficiencia del nitrógeno de los fertilizantes es baja; aproximadamente un tercio del fertilizante nitrogenado aplicado se pierde en la atmósfera o se filtra hacia aguas subterráneas en forma de amoniaco, óxido nitroso y nitratos; por tanto, se ha sugerido el uso de varias estrategias para mejorar la eficiencia de la fertilización nitrogenada y reducir las pérdidas de N en el ambiente (Prasad, 2013;Sharma and Bali, 2017;Yadav et al, 2017;Zhao et al 2019).…”
Section: Introductionunclassified